Fostering Social Justice Through Managing Civil Law Clinic in Indonesia: A Comprehensive Framework and Practice - Widiatedja, I Gusti Ngurah Parikesit (Jurnal Mulawarman Law Review, 2018)
The development of Clinical Legal Education (CLE) in Indonesia will significantly contribute for graduating more competent and more professional students as it equally combines knowledge, skills and value that reflects what lawyer do (practical skill), what lawyer should do (value), and how lawyer should do (knowledge) in legal cases. As a part of CLE, the existence of civil law clinic plays important role for enhancing the competency of law students. Nationally, some aspects of civil law significantly contribute to the fulfillment of basic human need in Indonesia. Specifically, contract law, family law, employment law, and consumer protection. Internationally, as an undeniable impact from globalization in Indonesia, this process requires harmonization of law that has adopted new concepts, practices, and legal institutions in Indonesia. Maintaining its existence, law schools in Indonesia should manage civil law clinics by designing planning stage, learning stage, and reflection stage. Planning stage consists: developing the objective; formulating Curriculum, preparing clinic member; organizing clinic in day-to-day basis; and establishing clinic Assessment and grading criteria. Next, in learning stage, it should combine the process of transfer of knowledge, skills, and values. Lastly, it should contain journaling, feedback and debriefing as a reflection stage. As a result, the existence of civil law clinic will foster social justice as an ultimate vision of clinical legal education in Indonesia.